Public-private partnerships for seed industry development in developing countries: Lessons from MasAgro maize in Mexico - Ciro Domínguez; Chittur S. Srinivasan; Arturo Silva-Hinojosa; Iraís Dámaris López-Becerril; Laura Donnet; Giacomo Zanello; Juan Burgueño (PLoS ONE, 2025)
Public-private partnerships (PPPs) are globally recognized for their potential to accelerate genetic improvement and delivery of new high-yielding seed varieties in developing countries. However, despite the strong advocacy for PPPs in crop improvement, there is little empirical evidence about their performance, capacities, and contribution to the development of seed industries and the promotion of competitive seed markets. This paper uses the experience of the MasAgro maize consortium, a PPP in Mexico, to examine crop variety innovation and delivery through PPPs, assess PPPs’ capacities to commercialize public germplasm-based varieties, and derive lessons for the design and implementation of future PPPs. Drawing on a combination of multiple data sources, we examined the PPP’s performance in the generation, dissemination, and commercialization of new maize hybrids. Our examination over the period 2011–2019 shows that the consortium was successful in maintaining a substantial flow of agronomically competitive maize hybrids, which compared favourably with the number of new varieties generated by national and international seed companies and the public sector. The partnership also contributed to refreshing and rejuvenating the variety portfolios of the consortium companies, which appear to have succeeded in bringing MasAgro varieties quickly into the market. However, seed sales achieved by MasAgro hybrids over this period remained small and multinational companies consistently maintained their leadership in the maize seed market. Our analysis shows that PPPs have strong capacities for the development of competitive seed varieties, but they face significant challenges in scaling up the uptake and adoption of these innovations in highly concentrated markets. To succeed in their objective of delivering affordable, high-quality seed on a large scale to smallholder farmers in developing countries, PPPs need to urgently incorporate a commercial and market-oriented perspective along all steps of the plant breeding and dissemination process.